Verbalization of the concept of “hearing” in Slavic languages - Liudmyla Pedchenko (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
The purpose of this study is to identify the most productive cognitive-nominative models that form the core of the nominative field of the concept “hearing” in Slavic languages. The object of the study is the Slavic names of auditory perception. The subject of the study is the onomasiological structure of these names.